Resilience of the electric grid through trustable IoT-coordinated assets - Vineet J. Nair; Priyank Srivastava; Venkatesh Venkataramanan; Partha S. Sarker; Anurag Srivastava; Laurentiu D. Marinovici; Jun Zha; Christopher Irwin; Prateek Mittal; John Williams; Jayant Kumar; H. Vincent Poor; et al. (Proceedings of the National Academy of Sciences, 2025)
The electricity grid has evolved from a physical system to a cyberphysical system with digital devices that perform measurement, control, communication, computation, and actuation. The increased penetration of distributed energy resources (DERs) including renewable generation, flexible loads, and storage provides extraordinary opportunities for improvements in efficiency and sustainability. However, they can introduce new vulnerabilities in the form of cyberattacks, which can cause significant challenges in ensuring grid resilience. We propose a framework in this paper for achieving grid resilience through suitably coordinated assets including a network of Internet of Things devices. A local electricity market is proposed to identify trustable assets and carry out this coordination. Situational Awareness (SA) of locally available DERs with the ability to inject power or reduce consumption is enabled by the market, together with a monitoring procedure for their trustability and commitment. With this SA, we show that a variety of cyberattacks can be mitigated using local trustable resources without stressing the bulk grid. Multiple demonstrations are carried out using a high-fidelity cosimulation platform, real-time hardware-in-the-loop validation, and a utility-friendly simulator.